Karya Kolosal Tari Bandungrejo dalam Rangka Hari Tari Dunia di Surakarta - Soemaryatmi, Soemaryatmi (PANGGUNG, 2018)
The aim of the research of the colossal artwork of Bandungrejo dance which was held on the 9th World Dance Day in ISI Surakarta is to description the information about the development of artistic creativity that has been developed in the community. The method that is used in this research involves the collection of data by using observation, interview, and documentation. The data processing is done by triangulation techniques. This study uses a sociological approach that considers art that the artwork is an expression of community groups.The research result showed that the colossal artwork of Bandungrejo dance is such a culmination of all of the artworks which is compiled into a dance masterpiece. The idea of this colossal folk dance is adopted from the legend of Ki Joko Bandung whose stages of presentation structure consisted of introduction, midle, climax and closing. It has wide range of motions which consists of symbolic motions, realist movements (daily-life motions) and motions of some customized characters. The musical composition that is used as a companion in the colossal dance is such a popular folk song, Ilir-ilir, Elo-elo narration, Gandrung Kemakmuran, Guyub Rukun Makaryo, and Langgam Rahina.Keywords: colossal work, folk dance, dance dayABSTRAK Tujuan penelitian karya kolosal tari Bandungrejo dalam Hari Tari Dunia ke-9 di ISI Surakarta adalah untuk mendeskripsikan perkembangan kreativitas seni yang ada di masyarakat. Metode penelitian yang digunakan meliputi pengumpulan data dengan teknik observasi, wawancara dan dokumentasi. Pengolahan data dilakukan dengan teknik trianggulasi. Penelitian menggunakan pendekatan sosiologi seni yang beranggapan bahwa karya seni merupakan ekspresi kelompok masyarakat. Hasil penelitian menunjukkan karya kolosal tari Bandungrejo merupakan kulminasi dari beberapa karya yang ada menjadi sebuah karya yang besar. Ide garap tari kolosal kerakyatan diangkat dari legenda Ki Joko Bandung. Struktur sajian terdiri dari bagian awal, tengah, klimaks dan penutup. Ragam gerak tari  yang digunakan sangat bervariasi terdiri dari gerak simbolis, gerak realis (sehari-hari) dan beberapa menyesuaikan dengan karakter tokoh yang ada. Komposisi musikal, lagu kerakyatan, Ilir-ilir,  Elo-elo Gandrung Kemakmuran dan Guyub Rukun Makaryo hingga langgam Rahina adalah Musik yang mengirinyaKata kunci;  karya kolosal, tari rakyat, hari tari.